(untitled) (Research, Society and Development, 2021)
The objetive is to analyze the fluctuations of temporal climate trends of precipitation and temperature between 1981-2019 for the city of Lagoa Seca, looking for possible damages of these fluctuations in socioeconomic activities, helping decision makers regarding possible risks. The climatic precipitation data were acquired from the Executive Agency of Water and Climate of the State of Paraíba for 1981 to 2019 and the thermal data was estimated by the Estima_T software for the same period of study. Rainfall irregularities between 2000-2019 registered ten dry years; six years too dry; three very rainy years and one rainy year, these rainfall irregularities lead us to conclude that climatic events and anthropogenic actions may be contributing to the records of these scenarios at a local scale, the predominance of dry and very dry years has impacted produce and produce which has been using longer times in irrigation. Studies with climate trends become more understandable when analyzing long time series which can be divided into sub-periods of at least 30 years. Rainfall anomalies between 2000-2019 recorded ten dry years; six years too dry; three very rainy years and one rainy year, these rainfall irregularities lead us to conclude that climatic events and anthropogenic actions may be contributing to the records of these scenarios at a local scale, the predominance of dry and very dry years has impacted produce and produce which has been using longer times in irrigation.